The gene task1 is involved in morphological development, mycoparasitism and antibiosis of Trichoderma asperellum. Issue 5 (4th May 2017) - Yang, Ping
ABSTRACT: Competitive activity, mycoparasitism and antibiosis of Trichoderma asperellum are considered essential mechanisms in its suppressive activity against soil-borne plant pathogens. The role of the mitogen-activated protein kinase encoding gene task1 on morphological development, mycoparasitic interaction and the production of cell wall degrading enzymes and secondary metabolites were examined in T. asperellum . The Δ task1 mutant had altered growth morphology, lost its ability to parasitise plant pathogens and showed increased expression of several cell wall degrading enzymes during confrontation with Rhizoctonia solani . T. asperellum task1 expression was negatively correlated with cell wall degrading enzyme activities during inducing experiments using pathogen cell wall compounds. In antibiosis assays, task1 deletion caused increased output of 6-pentyl-α-pyrone and inhibition of pathogen growth.